1989
DOI: 10.1148/radiology.172.3.2772190
|View full text |Cite
|
Sign up to set email alerts
|

Sports-related muscle injuries: evaluation with MR imaging.

Abstract: Sports-related muscle pain is frequent in both trained and untrained persons; however, its severity and significance may be difficult to assess clinically. The authors used magnetic resonance (MR) imaging to evaluate acute strains and delayed-onset muscle soreness in sedentary subjects and postmarathon myalgia in trained runners. MR imaging documented the distribution of affected muscles and the absence of focal hematoma, fascial herniation, subsequent fibrosis, and fatty infiltration. Pain associated with str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
75
1
2

Year Published

1992
1992
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(82 citation statements)
references
References 0 publications
4
75
1
2
Order By: Relevance
“…74 ,75 In both DOMS and strains, perifascial fluid collections are sometimes seen in the early phase of injury (see Chapters 25 and 33). 74 These recede as symptoms abate and creatine kinase and other enzyme levels normalize. The similarity in MRI appearances of strains and DOMS makes it difficult to distinguish between the two syndromes on the basis of MRI change alone.…”
Section: Delayed Onset Muscle Sorenessmentioning
confidence: 99%
“…74 ,75 In both DOMS and strains, perifascial fluid collections are sometimes seen in the early phase of injury (see Chapters 25 and 33). 74 These recede as symptoms abate and creatine kinase and other enzyme levels normalize. The similarity in MRI appearances of strains and DOMS makes it difficult to distinguish between the two syndromes on the basis of MRI change alone.…”
Section: Delayed Onset Muscle Sorenessmentioning
confidence: 99%
“…On the other hand, MRI is the procedure of choice for complex injuries and for prognostication, in particular with respect to high-performance sports [6], since these injuries require exact assessment of the length of the muscle tear, and is reproducible when evaluating progress. A muscular edema verified by MRI can last longer than the actual pain, and can indicate increased vulnerability of the muscle [20]. In addition to the presence of a hematoma, the longitudinal extension of a muscle tear is a decisive predictor of lost playing time (r = 0.58; p < 0.0001) [21]; this downtime can be underestimated by ultrasonography [22].…”
Section: Muscular Injuries In the Groin Region And Apophyseal Injuriesmentioning
confidence: 99%
“…Measures of the longitudinal lengths as well as percentage and volume of muscle injury (Connell et al 2004) in MRI are strong predictors of the time to return to play. It has been suggested that persistence of oedema defines the period of increased vulnerability to develop a re-tear (Fleckenstein et al 1989). MRI is also more sensitive in monitoring muscle healing compared with US (Fleckenstein et al 1989).…”
Section: Introduction and Pulse Sequencesmentioning
confidence: 99%
“…It has been suggested that persistence of oedema defines the period of increased vulnerability to develop a re-tear (Fleckenstein et al 1989). MRI is also more sensitive in monitoring muscle healing compared with US (Fleckenstein et al 1989).…”
Section: Introduction and Pulse Sequencesmentioning
confidence: 99%